Gentrification, paysages et sports de nature dans le New West états-unien - Gabrielle Saumon; Frédéric Richard (Projets de Paysage)
This paper is the result of a research program on rural gentrification in the American New West. It reports on an empirical and inductive research experience. In the discovery of its landscapes the New West appears more complex and heterogeneous than suggested in the literature. Based on qualitative interviews and field observations which made it possible to present a cross-section of landscapes from Montana to Colorado, the article re-examines this geography of the New West with the intention of sharing it with a French-speaking readership. In concrete terms, the New West is characterised by the omnipresence of nature sports in public and private spaces and essentially in the most attractive sites. The article also invites a social and critical interpretation of the landscape of the New West and its intrinsic inequalities thus establishing the hypothesis of a spatialised habitus. Through permanently installed facilities or through the visibility of more ephemeral practices, the practitioners of nature sports, through their behaviour and actions, integrate the latter in landscapes that have become socially distinctive and characteristic of the gentrification process.